Hotter and Weaker Mediterranean Outflow as a Response to Basin-Wide Alterations. - García-Lafuente, Jesús; Sammartino, Simone; Huertas, Emma; Flecha, Susana; Sánchez-Leal, Ricardo; Naranjo-Rosa, Cristina Belén; Nadal, Irene; Bellanco, María Jesús (Frontiers, 2021)
Time series collected from 2004 to 2020 at an oceanographic station located at the westernmost sill of the Strait of Gibraltar to monitor the Mediterranean outflow into the North Atlantic have been used to give some insights on changes that have been taking place in the Mediterranean basin. Velocity data indicate that the exchange through the Strait is submaximal (that is, greater values of the exchanged flows are possible) with a mean value of −0.847 ± 0.129 Sv and a slight trend to decrease in magnitude (+0.017 ± 0.003 Sv decade−1 ). Submaximal exchange promotes footprints in the Mediterranean outflow with little or no-time delay with regards to changes occurring in the basin. An astonishing warming trend of 0.339 ± 0.008◦C decade−1 in the deepest layer of the outflow from 2013 onwards stands out among these changes, a trend that is an order of magnitude greater than any other reported so far in the water masses of the Mediterranean Sea. Biogeochemical (pH) data display a negative trend indicating a gradual acidification of the outflow in the monitoring station. Data analysis suggests that these trends are compatible with a progressively larger participation of Levantine Intermediate Water (slightly warmer and characterized by a pH lower than that of Western Mediterranean Deep Water) in the outflow. Such interpretation is supported by climatic data analysis that indicate diminished buoyancy fluxes to the atmosphere during the seven last years of the analyzed series, which in turn would have reduced the rate of formation of Western Mediterranean Deep Water. The flow through the Strait has echoed this fact in a situation of submaximal exchange and, ultimately, reflects it in the shocking temperature trend recorded at the monitoring station
CC BY
Keywords: Corrientes marinas - Mediterráneo; Mares y océanos - Temperatura; Oceanografía - Observaciones; Strait of Gibraltar; Warming trend; Acidification; Mediterranean outflow; Levantine intermediate water; Western Mediterranean deep water